Post-democracy after the crises - Crouch, Colin 1944- (Polity, 2020)
"Crouch's provocative argument in Post-Democracy has in many ways been vindicated by recent events, but these have also highlighted some weaknesses of the original thesis and shown that the situation today is even worse"--
Keywords: Geschichte 2008-2020; Postdemokratie; Democracy / Philosophy; World politics / 21st century; World politics; 2000-2099